Moving places : relations, return, and belonging - Bon, Nataša Gregorič; Repič, Jaka (EASA series, 2016)
Moving Places draws together contributions from Europe, Latin America, Asia, and Africa, exploring practices and experiences of movement, non-movement, and place-making. The book centers on "moving places": places with locations that are not fixed but relative. Locations appearing to be reasonably stable, such as home and homeland, are in fact always subject to practices, imaginaries, and politics of movement. Bringing together original ethnographic contributions with a clear theoretical focus, this volume spans the fields of anthropology, human geography, migration, and border studies, and serves as teaching material in related programs